Penerapan Green Economy sebagai Pengembangan Wisata Alam Parsariran dalam Mewujudkan Pembangunan Berwawasan Lingkungan - Wisnu Yusditara; Silviana Batubara; Fithra Maharani; Makhrani Makhrani (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Green economy is a new concept that aims to improve economic aspects through development activities that do not neglect environmental sustainability. Batang Toru sub-district has various tourist objects, most of which are tourist objects that are only concerned with strategic locations. However, currently Batang Toru District is developing a tourist village that highlights agriculture and the natural beauty of the countryside. The purpose of this study is to describe and analyze the application of the green economy concept in the development of Parsariran Nature Tourism as an effort to realize environmentally sound development as well as supporting and inhibiting factors in the development of Parsariran Nature Tourism. This research is a qualitative descriptive research method. The Batang Toru sub-district government must immediately deal with land degradation and waste problems, such as helping to procure organic fertilizer for farmers.